(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
The paper examines the pedagogical and psychological aspects of developing sanogenic thinking in students, with a focus on cognitive, motivational, and emotional qualities, as well as methods that enhance emotional resilience and creative activity within the learning process.